Internal Evaluation in Academic Libraries a Case Study of Tarbiat Moalem University of Azerbaijan - Rahim Shahbazi; Dr. Kamran Sedaghat (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2008)
The aim of this research is to do an Internal Evaluation of the Academic library based on the views of experts to identify the current situation. It also aims to present a method for library evaluation and to help the planners and managers of such centers to understand and improve the condition of university libraries and information centers. The methodology of this case study is based on Internal Evaluation. Questionnaire, interview and checklists were used for gathering data. The results show that the lowest rates of Factors, belongs to the Services & Instruction Factor (%39) and the Budget Factor (%45) in the Factors are: Administration (%55.5), Staff (%58). Resources (%48), Material Organizing (%58),